3-(1′-Cyclobutylspiro[4H-1, 3-benzodioxine-2, 4′-piperidine]-6-yl)-5, 5-dimethyl-1, 4-dihydropyridazin-6-one (CEP-32215), a new wake-promoting histamine H3 antagonist/inverse agonist. (July 2016) - Hudkins, Robert L.; Gruner, John A.; Raddatz, Rita; Mathiasen, Joanne R.; Aimone, Lisa D.; Marino, Michael J.; Bacon, Edward R.; Williams, Michael; Ator, Mark A.
Abstract: CEP-32215 is a new, potent, selective, and orally bioavailable inverse agonist of the histamine H3 receptor (H3 R) with drug-like properties. High affinity in human (hH3 R Ki  = 2.0 ± 0.2 nM) and rat (rH3 R Ki  = 3.6 ± 0.7 nM) H3 R radioligand binding assays was demonstrated. Potent functional antagonism (Kb  = 0.3 ± 0.1 nM) and inverse agonism (EC50  = 0.6 ± 0.2 nM) were demonstrated in [ 35 S]guanosine 5 ′ -O-(γ-thio)-triphosphate binding assays. Oral bioavailability and dose-related exposure was consistent among rat, dog, and monkey. After oral dosing, occupancy of H3 R by CEP-32215 was estimated by the inhibition of ex vivo binding in rat cortical slices (ED50  = 0.1 mg/kg p.o.). Functional antagonism in brain was demonstrated by the inhibition of R-α-methylhistamine-induced drinking in the rat dipsogenia model (ED50  = 0.92 mg/kg). CEP-32215 significantly increased wake duration in the rat EEG model at 3–30 mg/kg p.o. Increased motor activity, sleep rebound or undesirable events (such as spike wave or seizure activity) was not observed following doses up to 100 mg/kg p.o., indicating an acceptable therapeutic index. CEP-32215 may have potential utility in the treatment of a variety of sleep disorders. This article is part of the Special Issue entitled 'Histamine Receptors'. Highlights: CEP-32215 is a new, potent and selective H3 R inverse agonist. Human H3 R Ki  = 2.0 with potent functional and inverse agonist activity (EC50  = 0.6 nM). Functional antagonism in the rat dipsogenia model (ED50  = 0.92 mg/kg p.o.). Active in the rat EEG model from 3 to 30 mg/kg p.o. with no undesirable events.